Televisi yang Memiliki Citra Islami: Antara Harapan dan Tantangan - Mabrur, Muhammad (Alhadharah: Jurnal Ilmu Dakwah, 2012)
Television today has been growing terribly fast.Â  The existence of an alternative channel that has the Islamic image and committed to deliver value-laden program is needed. So that viewers have a choice in determining the program to watch. In this short paper the writer will explain Islam TV chances to survive in the midst of competition among television stations and the steps should be considered to materialize these expectations. Some viewers reject the emergence of insertednegative-values TV, but they have to watch the shows because there is no an alternative.Â  The program provided by television with Islamic image can give an alternative. However, the sustainability of this television program depends on the alertness and creativity of the existing media players. They should strive to innovate with creative efforts, so that the audience can be entertained and satisfied with watching shows on offer.